Efeito de inibidores da ciclooxigenase sobre o transporte ileal de água e eletrólitos em ratos anestesiados - Previdelli, Ivna Hitzschky Silva dos Fernandes Vieira (2011)
The aim of this study was to evaluate the effects of selective and non-selective COX inhibitors on water and electrolyte transport and the villous/crypt ratio in the ileum of anesthetized rats. Thirty-six animals distributed in 6 groups were treated with 3mg/Kg ketorolac (a selective COX-1 inhibitor), 10mg/Kg celecoxib (a selective COX-2 inhibitor), 5mg/Kg indometacin (a non-selective COX inhibitor),ketorolac+celecoxib, 0.9% saline solution or phosphate buffer for 3 consecutive days. Ketorolac and celecoxib were diluted in 0.9% saline solution, while indometacin was diluted in phosphate buffer. Following 24 hours of fasting with access to water ad libitum, the animals were anesthetized with 1.2mg/Kg urethane i.p. and submitted to median laparotomy to isolate an ileal segment for perfusion. Cannulae were introduced through surgically created fistulas in the proximal and distal extremities of the segment. Perfusion was performed with modified Ringer solution containing 50mg/L phenolsulfonphthalein (a non-absorbable marker). After 40 minutes, 3 samples of perfusate were collected. In addition, 3 control samples were collected at baseline and by the end of the experiment for comparison of sodium, potassium and chloride concentrations (mmol/L). Finally the animals were euthanized, the extremities of the perfused segment were cut off (5-mm rings) for histopathological examination and the segment was weighed. After 48 hours of storage at 100oC, the segment was weighed again in order to correct the functional parameters. The administration of ketorolac promoted secretion of ileal water, sodium, potassium and chlorine. However, treatment with celecoxib alone or with ketorolac, and indomethacin treatment did not induce significant changes in the secretion of water, sodium, potassium and chlorine, when compared with control groups. In the histological evaluation, treatment with celecoxib alone or in combination with ketorolac, induced an increase in villous / crypt ration. On the other hand, ketorolac administration did not change the villous / crypt ration when we compared with the control. Indomethacin treatment induced a decrease in villous / crypt ration compared with the control. Based on these data we can conclude that inhibition of COX-1 by ketorolac, but not COX-2 inhibition by celecoxib, induced a functional change in the ileal water and electrolytes secretion, since there was not epithelial damage in the histological analysis of intestine of rats treated with ketorolac.